The genome and antigen proteome analysis of Spiroplasma mirum - Liu, Peng; Li, Yuxin; Ye, Youyuan; Chen, Jiaxin; Li, Rong; Zhang, Qinyi; Li, Yuan; Wang, Wen; Meng, Qingguo; Ou, Jingyu; Yang, Zhujun; Sun, Wei; et al. (Frontiers in Microbiology, 2022)
Spiroplasma mirum, small motile wall-less bacteria, originally isolated from a rabbit tick and had an ability to infect the newborn mice and caused cataract. This study, the whole genome and antigen proteins of S. mirum were comparative analyzed and investigated. Glycolysis, pentose phosphate pathway, arginine metabolism, nucleotide biosynthesis and citrate fermentation were found in S. mirum, while trichloroacetic acid, fatty acids metabolism, phospholipid biosynthesis, terpenoid biosynthesis, lactose-specific PTS and cofactors synthesis were completely absent. The Sec systems of S. mirum consist of SecA, SecDF, SecG, SecY and YidC. Signal peptidase Ⅱ was identified in S. mirum, but no signal peptidase Ⅰ. The relative gene order in S. mirum is largely conserved. Genome analysis of available species in Mollicutes revealed that they shared only 84 proteins. S. mirum genome has 381 pseudogenes, accounting for 31.6% of total protein-coding genes. This is the evidence that spiroplasma genome is under an onging genome reduction. Immunoproteomics, a new scientific technique combining proteomics and immunological analytical methods, provided the direction of our research on S. mirum. We identified 49 proteins and 11 proteins (9 proteins in common) in S. mirum by anti-S. mirum serum and negative serum, respectively. 40 proteins in S. mirum were identified relation with the virulence. All these proteins may play key roles in the pathogeny and can be used in the future for diagnoses and prevention.